Second-year results from CINEMA: A novel, patient-centered, team-based intervention for patients with Type 2 diabetes or prediabetes at high cardiovascular risk - Ian J. Neeland; Ala' Arafah; Brendan Bourges-Sevenier; Jean-Eudes Dazard; Zainab Albar; Zoe Landskroner; Nour Tashtish; Elke Eaton; Janice Friswold; Jodie Porges; Matthew Nennstiel; Amanda Davies; et al. (Elsevier, 2024)
Background: The care for patients with type 2 diabetes mellitus (T2DM) necessitates a multidisciplinary team approach to reduce cardiovascular (CV) risk but implementation of effective integrated strategies has been limited. Methods and Results: We report 2-year results from a patient-centered, team-based intervention called CINEMA at University Hospitals Cleveland Medical Center. Patients with T2DM or prediabetes at high-risk for CV events, including those with established atherosclerotic CVD, elevated coronary artery calcium score ≥100, chronic heart failure with reduced ejection fraction, chronic kidney disease (CKD) stages 2-4, and/or prevalent metabolic syndrome were included. From May 2020 through September 2022, 426 patients were enrolled in the CINEMA program. A total of 227 (54%) completed ≥1 follow-up visit after an initial baseline visit with median (IQR) follow-up time 4 [3-7] months with maximum follow-up time 19 months. Mean age was 60 years, 47 % were women, and 37 % were Black and 85% had prevalent T2DM, 48 % had established ASCVD, 29% had chronic HF, 27% had CKD and mean baseline 10-year ASCVD risk estimate was 25.1 %; baseline use of a SGLT2i or GLP-1RA was 21 % and 18 %, respectively. Patients had significant reductions from baseline in body weight (-5.5 lbs), body mass index (-0.9 kg/m2), systolic (-3.6 mmHg) and diastolic (-1.2 mmHg) blood pressure, Hb A1c (-0.5 %), total (-10.7 mg/dL) and low-density lipoprotein (-9.0 mg/dL) cholesterol, and triglycerides (-13.5 mg/dL) (p<0.05 for all). Absolute 10-year predicted ASCVD risk decreased by ∼2.4 % (p<0.001) with the intervention. In addition, rates of guideline-directed cardiometabolic medication prescriptions significantly increased during follow-up with the most substantive changes seen in rates of SGLT2i and GLP-1RA use which approximately tripled from baseline (21 % to 57 % for SGLT2i and 18 % to 65 % for GLP-1RA, p<0.001 for both). Conclusions: The CINEMA program, an integrated, patient-centered, team-based intervention for patients with T2DM or prediabetes at high risk for cardiovascular disease has continued to demonstrate effectiveness with significant improvements in ASCVD risk factors and improved use of evidence-based therapies. Successful implementation and dissemination of this care delivery paradigm remains a key priority.